2000
DOI: 10.1152/ajpheart.2000.279.4.h1737
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial activation during ventricular fibrillation in normal and failing canine hearts

Abstract: Because congestive heart failure (CHF) promotes ventricular fibrillation (VF), we compared VF in seven dogs with CHF induced by combined myocardial infarction and rapid ventricular pacing to VF in six normal dogs. A noncontact, multielectrode array balloon catheter provided full-surface real-time left ventricular (LV) endocardial electrograms and a dynamic color-coded display of endocardial activation projected onto a three-dimensional model of the LV. Fast Fourier transform (FFT) analysis of virtual electrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(57 reference statements)
2
5
0
Order By: Relevance
“…When the heart failure dog model also included a healed myocardial infarction, the DFs during VF were similar to those of controls, but the heart failure model had a decreased number of wave fronts as observed with noncontact mapping. 37 The present study shows data that supports the finding by Huang et al and Moreno et al by also showing a slower activation rate in the heart failure animals because, on average, the DFs were lower than in the control or ischemia animals. However, the present study also showed that a stable mechanism can exist in the CHF dogs of either reentry or focal.…”
Section: Everett Et Alsupporting
confidence: 93%
“…When the heart failure dog model also included a healed myocardial infarction, the DFs during VF were similar to those of controls, but the heart failure model had a decreased number of wave fronts as observed with noncontact mapping. 37 The present study shows data that supports the finding by Huang et al and Moreno et al by also showing a slower activation rate in the heart failure animals because, on average, the DFs were lower than in the control or ischemia animals. However, the present study also showed that a stable mechanism can exist in the CHF dogs of either reentry or focal.…”
Section: Everett Et Alsupporting
confidence: 93%
“…Previous experimental studies in the open-chest dog showed that VF in HF is associated with a significantly lower number of wavefronts and reentrant circuits than in normal hearts [2,7]. Our data showing decrease in the density of SPs and rotors in the ovine model of HF confirm those results.…”
Section: Hf Remodelling and Vfsupporting
confidence: 90%
“…During virtual endocardial mapping, Pierpont et al [7] showed no difference in peak frequency between HF and normal hearts. In contrast, Huang et al [2], using an epicardial multi-electrode plaque reported a 27% reduction in activation rate in HF.…”
Section: Hf Remodelling and Vfmentioning
confidence: 98%
See 1 more Smart Citation
“…When two wavefronts collided and fused, they were then counted as one. Conversely, when a wavefront bifurcated, two wavefronts were present from then on 20,21 . To quantify the number of distinct wavefronts present at any time on the endocardial surface of the atrium, color potentials projected onto the electroanatomic map of the atrium were set such that white represented a small range of amplitudes indicative of the most negative potentials present, and a rainbow spectrum represented progressively more positive potentials.…”
Section: Methodsmentioning
confidence: 99%